EFFECT OF USING VARIOUS TRAINING METHODS ON SOME FUNCTIONAL VARIABLES AND ACHIEVEMENT IN 50-METER MEN BREASTSTROKE RACE - Saleh Nayef Abdulhaleem (Universitas Negeri Jakarta, 2025)
Background. Swimming performance, particularly in short-distance events such as the 50-meter breaststroke, requires the integration of high physical efficiency, optimal physiological function, and precise technical execution. Objective. This study aimed to examine the effect of using various training methods on selected functional variables—maximum vital capacity (VC), maximum oxygen consumption (VO₂ max), and resting heart rate—and on the competitive performance of male swimmers in the 50-meter breaststroke. Methods. An experimental design with equivalent control and experimental groups was employed, using pre- and post-tests to measure outcomes. The sample consisted of 20 competitive male swimmers, equally divided into two groups. The experimental group participated in an 8-week training program incorporating resistance belts, buoyancy devices, breathing exercises, and complementary dry-land workouts, conducted four times per week. The control group followed a conventional training regimen. Data were collected using standardized tests: a spirometer for VC, a modified swimming test for VO₂ max, a pulse oximeter for resting heart rate, and a digital stopwatch for race completion time. Results. The results revealed statistically significant improvements in the experimental group across all variables, including increased VC and VO₂ max, reduced resting heart rate, and faster race times, with no significant changes observed in the control group. Conclusions. The study concludes that integrating diverse training methods significantly enhances both functional physiological capacity and competitive performance in short-distance swimmers. This research contributes to sports science by providing empirical evidence that a multi-modal training approach can yield superior adaptations compared to traditional methods, offering practical guidance for coaches aiming to optimize athlete performance in sprint swimming events.